2019
DOI: 10.21426/b635048595
|View full text |Cite
|
Sign up to set email alerts
|

The geographic distribution of Protura (Arthropoda: Hexapoda): a review

Abstract: Protura is a poorly known class of Hexapoda represented by more than 800 species belonging to 77 genera worldwide. They are tiny soil organisms with low dispersal ability, mainly attributable to water and human-mediated transfer. The analysis of biogeography of Protura is hindered by the lack of knowledge on their natural history, systematics and distribution. In order to provide a starting point for future more detailed investigations, we reviewed the available literature on their geographic distribution, mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
2
6
0
4
Order By: Relevance
“…We showed that the distribution ranges of both soil and cave Eukoenenia species are very narrow even when compared to other subterranean species, and that range size does not significantly differ between the two guilds here considered. This suggests a limited dispersal potential for most species, as also empirically observed for other small‐sized soil‐ and cave‐dwelling specialists, such as proturans (Galli & Rellini, 2020) and diplurans (Sendra et al, 2020). An anecdotal example of this low dispersal ability can be found in the case of Eukoenenia maquinensis and E. sagarana , two cave‐adapted palpigrades from Brazil.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…We showed that the distribution ranges of both soil and cave Eukoenenia species are very narrow even when compared to other subterranean species, and that range size does not significantly differ between the two guilds here considered. This suggests a limited dispersal potential for most species, as also empirically observed for other small‐sized soil‐ and cave‐dwelling specialists, such as proturans (Galli & Rellini, 2020) and diplurans (Sendra et al, 2020). An anecdotal example of this low dispersal ability can be found in the case of Eukoenenia maquinensis and E. sagarana , two cave‐adapted palpigrades from Brazil.…”
Section: Discussionsupporting
confidence: 62%
“…It is worth noting that continental-wide distribution has been observed in other soil-dwelling specialists; for example, these patterns can emerge as the result of continental drift paralleled by slow evolution, as in the amphi-Atlantic distributions of Protura (Galli & Rellini, 2020). In our case, the two most significant outliers are E.…”
Section: Distribution Patterns and Ecologysupporting
confidence: 49%
See 2 more Smart Citations
“…This size difference was evidenced also in other species of Acerentomidae like Acerentulus shrubovychae Galli & Capurro, 2013 and Acerentulus tortii Galli et al, 2017. The existence of species complexes in Protura was already suggested by Fratello & Sabatini (1989) on the basis of differences between kariotypes of different Eosentomon transitorium Berlese, 1908a populations. A species-level diversifi cation can also be assumed for allopatric populations of some species that were likely separated by ancient vicariance events, as it is the case in the amphi-Atlantic Delamarentulus tristani (Silvestri, 1938) (see Galli & Rellini, 2020). Theoretically DNA barcoding could be an excellent tool to distinguish cryptic species, and in some cases it was used for that purpose since the early days (e.g.…”
Section: Discussionmentioning
confidence: 99%